Polar oceans governance in an era of environmental change - Stephens, Tim; VanderZwaag, David L.; Edward Elgar Publishing (Cheltenham, UK : Edward Elgar, 2014)
'As climate change thrusts the Arctic and Antarctic towards the top of the global political agenda, this timely collection provides a broad overview of the issues, the options, and the rules and institutions that are already in place.'--Michael Byers, University of British Columbia, Canada and author of International Law and the Arctic.'While at opposite ends of the earth, the shared characteristics of the Arctic and Antarctic are identified by this multidisciplinary collection of essays. Both regions need effective, flexible governance--whether through the Antarctic Treaty System or the Arctic Council--if they are to respond to the challenges of commercialization of hydrocarbons, climate change and the marine environment. Internationally recognized scholars grapple with the global politics of the polar regions, the perspectives of the Inuit people and the role of joint development. This invaluable, well-researched and stimulating collection clarifies the geopolitical and socio-economic dynamics of some of the world's most fragile and vulnerable environments.'--Gillian Triggs, Australian Human Rights Commission. This timely book provides a cutting-edge assessment of how the dynamic ocean regions at the highest latitudes on Earth are being managed in an era of unprecedented environmental change. The Arctic and Southern Oceans are experiencing transformative environmental change as a result of climate change and ocean acidification. As areas of unparalleled environmental, cultural and scientific value, they are crucibles for testing how integrated, eco-systemic governance frameworks can be developed to meet and address volatile environmental, political and economic challenges. Drawing especially on Australian and Canadian experiences in polar oceans management through multilateral global and regional institutions, the book identifies policy options for improving the governance of the Arctic and Southern Oceans. In offering a pioneering'bipolar' assessment of environmental management at both polar regions, this important book will be an essential resource for policy-makers, scholars and students actively engaged in discussion and debate on the future of polar oceans governance in the Anthropocene.--
Pt. I. Environmental change in the polar oceans -- pt. II. Geostrategic dynamics in the polar oceans -- pt. III. Resources, environment, sovereignty and jurisdiction -- bipolar perspectives -- pt. IV. Developing national and foreign policy responses -- pt. V. The future of polar oceans governance.
Includes bibliographical references and index.
Keywords: Climatic changes -- Environmental aspects -- Polar regions; Oceanography -- Polar regions